Prognostic value of lactate dehydrogenase-to-albumin ratio in metastatic/recurrent pancreatic cancer treated with first-line gemcitabine plus nab-paclitaxel: a single-center retrospective cohort study - Yamauchi, Yoshiya; Sofuni, Atsushi; Nagakawa, Yuichi; Itoi, Takao (Journal of Gastrointestinal Oncology; Vol 17, No 3 (June 29, 2026): Journal of Gastrointestinal Oncology, 2026)
Background: Prognostic stratification at the initiation of chemotherapy is clinically important in patients with metastatic or recurrent unresectable pancreatic cancer. The lactate dehydrogenase-to-albumin ratio (LAR) is an objective blood-based index that combines tumor-associated activities with systemic conditions of the host; however, evidence of its usefulness as a prognostic index in patients receiving first-line gemcitabine plus nab-paclitaxel (GnP) remains limited. In this study, we evaluated the prognostic value of baseline LAR in these patients.Methods: This single-center retrospective cohort study included consecutive patients with metastatic or recurrent unresectable pancreatic cancer who underwent first-line GnP between 2015 and 2024. Baseline LAR was calculated from laboratory data obtained within 7 days before treatment initiation, and neutrophil-to-lymphocyte ratio (NLR) was evaluated as a comparative inflammatory marker. The primary analysis evaluated the association between baseline LAR and overall survival (OS) using prespecified multivariable Cox proportional hazards models. The functional form of LAR was examined using restricted cubic splines (RCS). Kaplan-Meier curves were then presented to visualize risk stratification by combining Eastern Cooperative Oncology Group performance status (ECOG PS) with LAR. The incremental prognostic performance beyond the base clinical model was evaluated using model fit and discrimination metrics, with bootstrap internal validation.Results: The final analytic cohort comprised 205 patients (median age, 67 years; 63.9% men). The median baseline LAR was 4.94. In the prespecified multivariable model, ECOG PS and LAR were independently associated with OS [PS 2 vs. 0: hazard ratio (HR), 2.38; 95% confidence interval (CI), 1.28–4.42; LAR per 1-standard deviation (SD) increase: HR, 1.29; 95% CI, 1.09–1.52]. RCS analysis demonstrated a significant overall association without evidence of nonlinearity (overall P=0.03; nonlinear P=0.71). Kaplan-Meier curves for four risk groups defined by PS (0–1 vs. 2) and LAR (below vs. at/above the median) showed significant separation (log-rank P